The Republic of Colombia : an account of the country its people, its institutions and its resources / by F. Loraine Petre, author of "Napoleon´s campaign in Poland, 1806-1807" with numerous illustrations and a map (1906)
"This voluem, making no pretensions to literary merit, merely seeks to collate such information as I have been able to gather regarding a country little known at present in England. Yet Colombia is beginning to attract the attention of investors and others who, I venture to hope, may find it useful to have, in a convenient form hitherto not available in English, some general informatión regarding the conditions and prospects, the resources and government, of the State. My personal knowledge of the country is confined to more or less beaten tracks, and some of the principal cities, including the capital. I trust that I have succeeded in avoiding the appearance of dogmatising on insufficient data. Nearly every opinion formed on my own impressions of the country has, before being enunciated, been submitted to the judgment of friends, English or Colombian, of greater experience"